PENGARUH KOMBINASI BAHAN PELICIN MAGNESIUM STEARAT DAN TALK DALAM PEMBUATAN TABLET GLIMEPIRID DENGAN TEKNIK PENCAMPURAN INTERAKTIF - Ilham Kuncahyo; Siti Aisiyah; Shabrina Nindya Hutami; RR Sri Wulandari (2026)
Homogeneity is one of the primary challenges in the formulation of tablets containing low-dose drugs such as glimepiride. The interactive mixing technique, in which the drug is adhered to a host carrier, has been developed as an innovative approach to address this issue. One of the essential excipients required in tablet manufacturing is a lubricant. The use of micronized lubricants, namely magnesium stearate and talc, plays a critical role in determining the outcome of the compression process of interactive mixture tablets. This study aimed to investigate the effect of magnesium stearate and talc as lubricants on the physical quality and dissolution behavior of glimepiride interactive mixture tablets. Five formulations were prepared using different proportions of magnesium stearate and talc: F1 (magnesium stearate : talc) = 1,25 : 0,75; F2 = 0,5 : 1,5; F3 = 0,25 : 1,25; F4 = 1,5 : 0,5; and F5 = 1 : 1. The host carrier was prepared by mixing Avicel PH 101 and lactose in a 1:1 ratio, followed by granulation using polyvinylpyrrolidone (PVP) as a binder. The lubricants were then blended with the host particles onto which glimepiride had been adhered, and the mixture was subsequently compressed using the direct compression method. The resulting tablets were evaluated for physical quality parameters, including friability, hardness, disintegration time, and dissolution. The data obtained from each formulation were statistically analyzed using SPSS version 12.0. The results demonstrated that all five formulations met the homogeneity requirements, with coefficient of variation (CV) values of less than 5%. The combination of magnesium stearate and talc significantly affected the physical quality and dissolution behavior of glimepiride interactive mixture tablets. Formula 4, which contained the highest proportion of magnesium stearate and the lowest proportion of talc compared to F1, F2, F3, and F5, produced tablets with greater hardness, reduced friability, prolonged disintegration time, and a slower dissolution rate.